If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2k + 8 = x + 5 Reorder the terms: 8 + -2k + 6x = x + 5 Reorder the terms: 8 + -2k + 6x = 5 + x Solving 8 + -2k + 6x = 5 + x Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -2k + -8 + 6x = 5 + -8 + x Reorder the terms: 8 + -8 + -2k + 6x = 5 + -8 + x Combine like terms: 8 + -8 = 0 0 + -2k + 6x = 5 + -8 + x -2k + 6x = 5 + -8 + x Combine like terms: 5 + -8 = -3 -2k + 6x = -3 + x Add '-6x' to each side of the equation. -2k + 6x + -6x = -3 + x + -6x Combine like terms: 6x + -6x = 0 -2k + 0 = -3 + x + -6x -2k = -3 + x + -6x Combine like terms: x + -6x = -5x -2k = -3 + -5x Divide each side by '-2'. k = 1.5 + 2.5x Simplifying k = 1.5 + 2.5x
| 8n^2=6 | | 294=18-y | | 35y^2-9y+3=0 | | 284=18-y | | 2m^2+27m-4=0 | | 2n+3=4n-7 | | 1.75x=4.2 | | 6n+12=20 | | 2m^2=10-2m | | (n+3)(2n+3)=0 | | 10+9x=10+x | | x^2+y^2+2*x+14*y-15=0 | | 2n^2=105-11n | | 10x-17=2x+10 | | 5.7-6/12 | | x(a-6b)=3m(x-c) | | 0=-16t+40t-84 | | 26-m=76 | | g(x)=x^5-9x^3 | | 6(15-3x)=120 | | -3(x+5)=-30 | | y=4(a)+3+2 | | 8(2+x)=80 | | 12321+231756= | | 2(5x-3)=74 | | -8a-(7b)= | | 6+50=-12 | | 5(x+9)=50 | | 6a+7=18 | | 100=(0.2)2/2 | | y=4(2)f(a)+2 | | y=4(a+3)+2 |